1991
DOI: 10.1029/91ja00568
|View full text |Cite
|
Sign up to set email alerts
|

Lower hybrid waves excited through linear mode coupling and the heating of ions in the auroral and subauroral magnetosphere

Abstract: Experimental observations on the ISIS 1, ISIS 2, ISEE 1, and DE 1 spacecraft demonstrate that strong lower hybrid (LH) waves can be excited by VLF electromagnetic (em) whistler mode waves as the em waves propagate through regions of the ionosphere and magnetosphere where small‐scale magnetic‐field‐aligned irregularities exist in the mean plasma density. There is strong evidence that the LH waves are excited by linear mode coupling as the em waves scatter from the irregularities. The present paper considers two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Contrary to this theory, Bell andNgo (1988, 1990) and Bell et al (1991) attribute the excited lower hybrid waves to EM whistler mode waves which are scattered from magnetic-field-aligned plasma density irregularities in the ionosphere (see Figure 3). These lower hybrid waves are supposed to be responsible of ion heating observed over powerful VLF transmitters by Dzhordzhio et at.…”
Section: Parametric Interactionmentioning
confidence: 97%
See 2 more Smart Citations
“…Contrary to this theory, Bell andNgo (1988, 1990) and Bell et al (1991) attribute the excited lower hybrid waves to EM whistler mode waves which are scattered from magnetic-field-aligned plasma density irregularities in the ionosphere (see Figure 3). These lower hybrid waves are supposed to be responsible of ion heating observed over powerful VLF transmitters by Dzhordzhio et at.…”
Section: Parametric Interactionmentioning
confidence: 97%
“…(1987). The physical mechanism of this process has been theoretically analyzed by Bell et al (1991). They found that the energy increase of both 1 eV H + ions and 16 eV O + ions could be ~50 eV.…”
Section: Parametric Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response of spherical electric antennas to LH waves has been investigated [ Temerin , 1978; Bell et al , 1991a, 1991b, 1994]. If I LH ( k , ω in ) is defined as the spectral intensity of the electric field of the lower hybrid waves, it can be shown [ Temerin , 1978; Bell et al , 1991a] that the electric field intensity, I V (ω), measured on a spherical electric antenna is related to I LH ( k , ω in ) through the integral equation: where k is the wave vector, R ( k ) = cos 2 β[sin2ζ/2ζ] 2 , β is the angle between k and l , l is a vector directed along the antenna with magnitude l , l is the antenna length, ζ = k · l /4, δ( x ) is the Dirac delta function, ω′ = ω − ω in , ω is the apparent frequency of the wave, ω in is the actual frequency of the input signal, and v s is the spacecraft velocity vector.…”
Section: Modelmentioning
confidence: 99%
“…cate that their wavelengths are seldom smaller than '2 m [Bell et al, 1983;Bell and Ngo, 1988;James and Bell, 1987;Bell and Ngo, 1990;Bell et al, 1991aBell et al, , 1991bBell et al, , 1994. Since the dipole antenna length proposed by Inan et al [2003] was roughly 100 m, we have a situation in which some of the waves of frequency w radiated by the antenna will possess wavelengths much longer than the antenna while other radiated waves of frequency w will possess wavelengths much shorter than the antenna.…”
Section: Introductionmentioning
confidence: 99%